STUDI KASUS IMPLEMENTASI PENGELOLAAN OPT DALAM RANGKA KEBERLANJUTAN EKOSISTEM PERTANIAN SERTA KAITANNYA TERHADAP PERAN PENYULUH DAN PRODUKTIVITAS PADI SAWAH DI KABUPATEN ASAHAN - Eryanto, Okto; Kuswardani, Retna Astuti; Noer, Zulhery (Universitas Wahid Hasyim, 2024)
Plant Pest Organisms play an important role in plant growth and productivity. Therefore, the role of extension workers is very important in encouraging farmers to adopt sustainable management of plant pest organisms. The analytical method used was a descriptive research method with a case study approach in three rice production center sub-districts, Asahan Regency with a total sample of 368 farmers. The research results found that farmers have carried out sustainable management of Plant Pest Organisms and achieved a balance effectiveness in controlling pests and environment.